Preliminary results of an Acceptance and Commitment Therapy (ACT) brief group intervention for psychosis. - Castilho, P (2015)
Acceptance and Commitment Therapy (ACT) is a contextual-behavioral therapy with promising results in various psychological disorders, including psychosis. This study aims to compare the potential benefits of a 4-session ACT group intervention with the interventions commonly offered in Portugal. ACT participants improved in a wider range of measures and 2 of the 3 patients improved significantly in both symptoms, cognitive processes and positive indicators of adjustment (without any deterioration). Future studies should explore the relationship between participants’ clinical profile and benefits from ACT interventions.